PENERAPAN MODEL PEMBELAJARAN TARGET-TASK PROBLEM SOLVING MENGGUNAKAN PENDEKATAN INKUIRI UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF DAN KEMAMPUAN PEMECAHAN MASALAH FISIKA SISWA MA - Hasili, Hastal (2017)
Penelitian ini bertujuan untuk mendapatkan gambaran mengenai peningkatan kemampuan kognitif dan kemampuan pemecahan masalah fisika siswa sebagai efek penerapan model pembelajaran Target - Task Pro blem Solving menggunakan pendekatan inkuiri . Penelitian ini menggunakan metode pre - experiment dengan desain one group pretest - posttest. Subyek penelitian sebanyak 22 orang siswa kelas X di salah satu Madrasah Aliyah di Kota Tasikmalaya pada Tahun Ajaran 2016/2017. Pengumpulan data menggunakan instrumen tes kemampuan kognitif berbentuk pilihan ganda dan tes kemampuan pemecahan masalah berbentuk uraian, lembar observasi untuk mengamati keterlaksanaan pembelajaran yang digunakan dalam pembelajaran, dan skal a sikap untuk tanggapan guru dan siswa terhadap penerapan model pembelajaran pada konsep fluida statis. Hasil penelitian menunjukkan bahwa penerapan model pembelajaran Target - Task Problem Solving dapat meningkatkan kemampuan kognitif dan kemampuan pemecaha n masalah fisika dengan nilai N - gain masing - masing sebesar 0,62 untuk kemampuan kognitif dan sebesar 0,66 untuk kemampuan pemecahan masalah. Terdapat hubungan yang positif dan signifikan antara kemampuan kognitif dengan kemampuan pemecahan masalah fisika s iswa dengan koefisien korelasi sebesar 0,87 dengan tingkat hubungan yang sangat kuat. Secara umum siswa memberikan tanggapan positip terhadap penerapan model pembelajaran Target - Task Problem Solving menggunakan pendekatan inkuiri . Kata Kunci : Model Target - Task Problem Solving, pendekatan inkuiri, kemampuan kognitif, kemampuan pemecahan masalah, A Target - Task Problem Solving learning model is implemented to get an overview high school students' cognitive and physics problem solving ability improvement in static fluid concept. This research uses pre - experiment method with one group pretest - posttest d esign . Twenty two tenth grade students of a senior high school in Tasikmalaya is involved as sample of this research. Data are collected using a written test instrument (pretest and posttest) for student' cognitive and problem solving ability, observation sheet to observe the feasibility study, and the attitude scale for students' responses to the lea rning implementation. We use multiple - choice questions ranged from C 1 to C 4 Bloom's cognitive to measure students' cognitive ability and open - ended questions t o measure student problem solving ability. The teacher and student activities in this implementation were all carried o ut as expected. The result s show that implementation of Target - Task Problem Solving learning model significantly improve s students' cogni tive and problem solving ability in static fluid concept. This is indicated by the means score of normalized gain <g> is 0,62 (medium category) for cognitive ability and the means score of normalized gain <g> is 0,66 (medium category) for students' problem solving ability respectively . We also find that there is correlation between students' cognitive and physics problem solving ability with correlation coefficient at 0,87 (significant). In addition , teachers and students respond positively to this learning implementation. These results indicate d that the Target - Task Problem Solving learning model is one of alternative learning models that can improve the high sc hool students' cognitive and problem solving ability of physics students . Keywords : T arget - task problem solving model, inquiry, students' cognitive ability, physics problem solving ability